Rotational speed analysis on double rotating cylinder for cylinder to flat plate using numerical method - Roslan, Muhammad Syakir Iman; Mohammad Ali, Hidayatullah; Mohd Rafie, Azmin Shakrine (Aeronautical and Astronautical Society of the Republic of China, Taiwan, 2023)
The cylinder-to-flat plate embedment is a new invention for the unmanned aerial vehicle which is intended to fly in the stratosphere region for surveillance purposes with the embedment of a double rotating cylinder and flat plate. This study was purposed to investigate the aerodynamic performance of the model. The performance of the model was examined using computational fluid dynamics software which is ANSYS Workbench 2020 to simulate 2D flow analysis with various rotational speeds for four cases of rotational direction at an angle of attacks from 00 to 200 with a fixed free stream velocity of 15 m/s. The best condition chosen for the model is 1000-1000 RPM with both cylinders rotating in a clockwise direction. The numerical analysis resulted that as the rotational speed increases, the lift coefficient increases, and the model delayed in stall angle up until 100 hence having a low drag coefficient at a higher angle of attack.